INTRAMEDULLARY SCREW FIXATION FOR PROXIMAL FIFTH METATARSAL ZONE II AND III FRACTURES ON ATHLETE POPULATION: A SYSTEMATIC REVIEW - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
As the most prevalent fracture of the foot, the fifth metatarsal fracture has the incidence of 6.7 per 100.000 persons each year mainly in the high-risk population such as athletes. While most of the cases resolved over time with conservative management, the fifth metatarsal region is prone to the risk of non-union due to the poor blood supply. Early treatment should immediately be given for the fracture to improve significantly and rapidly. Currently, intramedullary screw fixation has become an emerging treatment to conventional plate fixation or K-wire in managing proximal fifth metatarsal fracture. Intramedullary screw fixation has demonstrated a minimally invasive approach with better outcomes and minimal complications. However, the review regarding the use of the approach in managing proximal fifth metatarsal zone II and III fractures in the athlete population is still scarce. The evidence as a base for recommendations to manage fifth metatarsal fracture thus limited. Therefore, this study is intended to review the summary and pitfalls of intramedullary screw fixation in the fifth metatarsal zone II and III in athletes to bring insight and improve the efficiency of the approach.